Proceedings of the 15th New Zealand Conference on Human-Computer Interaction 2015
DOI: 10.1145/2808047.2808057
|View full text |Cite
|
Sign up to set email alerts
|

Simulating Electricity Consumption Pattern for Household Appliances using Demand Side Strategies

Abstract: This paper investigates research work related to the modelling and simulation of household electricity consumption with a view to developing a simulation to evaluate the effectiveness of demand-side management mechanisms. The eventual aim of the research is to be able to model household consumption down to the level of individual appliance use in order to explore and assess the impact of different demand-side strategies, both in individual household consumption, and on overall grid balance. The focus of this p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…In our previous works on synthesising residential electricity load profiles [28,[35][36][37], we found that appliances are mainly used to synthesize domestic load profiles. In accordance with what was revealed in [15], there is a need to incorporate the consumption patterns of electrical appliances into DSM models. It is also essential to focus on appliance usage patterns to improve our understanding of the impacts and characteristics of individual appliances, as mentioned in [38].…”
Section: Introductionmentioning
confidence: 55%
See 2 more Smart Citations
“…In our previous works on synthesising residential electricity load profiles [28,[35][36][37], we found that appliances are mainly used to synthesize domestic load profiles. In accordance with what was revealed in [15], there is a need to incorporate the consumption patterns of electrical appliances into DSM models. It is also essential to focus on appliance usage patterns to improve our understanding of the impacts and characteristics of individual appliances, as mentioned in [38].…”
Section: Introductionmentioning
confidence: 55%
“…One load-management strategy in DSM is load-shifting (Figure 1), a technique to shift peakhour demand to off-peak hours by reallocating the load demand [6] without changing the total energy consumption [7]. This can also reduce the cost [1,6,[8][9][10][11][12][13][14][15] as well as the capacity of the electricity grid. In practice, Yilmaz et al (2019), quoted in [16], defined load-shifting as a "process where consumers time-shift demand, either through behaviour change or automation, in response to particular conditions within the electricity system, and [it] is therefore a potential solution to equilibrate the network".…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation